Modification of a Rice Cooker into Black Garlic Aging Chamber and Performance Analysis - Ussy Siti Qudsiyah; Dias Indrasti; Tjahja Muhandri (Jurnal Keteknikan Pertanian, 2025)
This study aimed to modify a conventional rice cooker into a temperature-controlled aging chamber for black garlic production. The modification involved disabling the automatic switch and replacing the internal sensor with an external DS18B20 sensor, connected to an STC-1000 digital thermostat. The system was designed to maintain consistent heating at three temperature settings: 60 °C, 70 °C, and 80 °C, and enabled real-time temperature monitoring using a thermo recorder. Results showed that the modified rice cooker with only a thermostat had a temperature fluctuation of 10.8 °C. When combined with 4 mm cardboard insulation, the fluctuation decreased significantly to 3.8 °C.